PENINGKATAN HASIL BELAJAR IPA MELALUI MODEL DISCOVERY LEARNING BERBASIS EKSPERIMEN PADA PESERTA DIDIK KELAS IV SD NEGERI DUREN SAWIT 13 PAGI - Zulfa Ainul Hikmah; Dina Rahmi Darman; Anggit Aruwiyantoko (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The implementation of science education in elementary schools still conventional teaching models. As a result, students are not sufficiently engaged in the learning process, and learning outcomes have not met the intended learning objectives. The experiment-based discovery learning model prioritizes students direct, independent engagement in the learning process to discover concepts through experimental activities. This study aims to determine the improvement in science learning outcomes through an experiment-based discovery learning model among fourth-grade elementary school students. The method used was Classroom Action Research (CAR), conducted in two cycles. Each cycle consisted of three stages: planning, implementation and observation, and reflection. The research subjects were 32 fourth grade elementary school students. Data collection was conducted through achievement tests, observations of teacher and student activities, interviews, and documentation. The research results indicate that the implementation of an experiment-based discovery learning model can improve science learning outcomes. This is evidenced by an increase in the achievement rate from 44% in the pre-cycle to 72% in Cycle I, and reaching 88% in Cycle II. In addition, students’ learning activities became more enthusiastic and active because they were directly involved in the discovery process through experimental activities. Based on these results, it can be concluded that the experiment-based discovery learning model can improve science learning outcomes among fourth-grade elementary school students.